'Byng Boys': A Profile of Senior Commanders of Canadian Combat Units on the Somme, 1916. (January 2016) - Stewart, William
This study provides a profile of the 107 officers who led Canadian combat units of battalion size or larger on the Somme, in 1916. It demonstrates that Canadian Militia officers dominated the command ranks, but they generally had limited or no formal military training or active service prior to the war. It highlights important differences in the rate of promotion, selection process, and influence of politics between the infantry and technical arms. The study also finds Canadian and Australian battalion commanders shared similar profiles and patterns in comparison to British battalion commanders.